Recent advances in animal nutrition 2008 - Garnsworthy, Philip C.; Wiseman, J. (Julian) (Nottingham University Press, 2009)
Authored by international experts in the animal-production industry, this record of the proceedings of the 42nd University of Nottingham Feed Conference explores topics such as the improvements of feed efficiency, the impact of biofuel co-products, the use of enzymes to increase nutritive value, and the techniques for coping with disease outbreaks.